Physical Education Teacher as A Reflective Practitioner Studying at a Sports University (Laisvalaikio tyrimai, 2018)
Research background. With the rapid advancement and changes in students’ generation, the society needs improvements in the process of the preparing physical education teachers. The process of the preparation requires the development of a practically, individually, creatively, critically minded physical education teacher capable of active and independent problem solving in practice. The article focuses on the process of preparation and improvement of the curriculum for physical education teachers in Lithuania. The aim of the article is to update and compare a new European dimension – a reflective teaching model that encourages the analysis of past activities and the construction of new activities. The aim of the research was to reveal theoretical assumptions about the application of the reflective model in the training of physical education teachers at a sports university. Conclusions and perspectives: It is important to reform the academic and practical content of studies by creating reflexive physical education teacher training, creating conditions for the reflection of personal and professional identity, developing and integrating reflective model approaches into the content of studies, developing teacher competencies, developing reflective analysis and cooperation and interaction with students in the areas of knowledge, skills and valuables. The reflective model in vocational training of specialists in the work of physical education teachers creates conditions for the development of changes and the search for alternative ways to attract students to enjoy physical activity and fulfill the goal of physical education – to be physically active not only within the school, but also outside it. This goal is developed at a university where universality is particularly emphasized. The argument for the purpose of physical education is part of the research as a training tool for the training of physical education teachers. A combination of practical work and research is necessary as it gives the educators the opportunity to learn themselves to understand their knowledge and maintain opinions. It would also help improve the sometimes extremely good status of the teacher of physical education and enhance the knowledge of the work of a physical education teacher in the practice of professional work.Keywords: physical education teacher, reflexive practice.